2006
DOI: 10.1111/j.1472-765x.2006.02018.x
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant staphylococcal colonization in clinically normal dogs and horses in the community

Abstract: Aims:  To evaluate the prevalence of methicillin‐resistant staphylococcal (MRS) colonization in clinically normal dogs and horses in the community. Methods and Results:  Three hundred clinically normal horses and 200 clinically normal dogs were enrolled. One nasal swab was collected from each horse. Two swabs were taken from each dog: (i) from an anterior nare, and (ii) a combination of the perineal area and 0·5 cm into the anus. Enrichment cultures were performed. Methicillin‐resistant Staphylococcus aureus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
95
5
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 31 publications
7
95
5
5
Order By: Relevance
“…The rate of nasal MRCNS carriage in horses (47.8%) was higher than those previously reported in the Netherlands (22%) [4], Japan (13 to 29.5%) [38,39], Slovenia (42%) [34] and Italy (35.2%) [9] but lower than those reported in Denmark (50 to 82%) [2,20]. In previous studies, colonization of horses with methicillin-resistant S. lentus and S. sciuri has been reported [2,4,9,20,38,39].…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…The rate of nasal MRCNS carriage in horses (47.8%) was higher than those previously reported in the Netherlands (22%) [4], Japan (13 to 29.5%) [38,39], Slovenia (42%) [34] and Italy (35.2%) [9] but lower than those reported in Denmark (50 to 82%) [2,20]. In previous studies, colonization of horses with methicillin-resistant S. lentus and S. sciuri has been reported [2,4,9,20,38,39].…”
Section: Discussioncontrasting
confidence: 47%
“…A high prevalence of methicillin-resistant staphylococci (MRS) colonization has also been reported in healthy horses in Europe [2,4,9,20,34] and Japan [38,39].…”
mentioning
confidence: 99%
“…Thus horses may act as a reservoir for this strain, perhaps mirroring the putative association of ST398 with pigs. In Slovenia, MRSA was absent from a total of 300 horses sampled with nasal swabs (Vengust et al, 2006); one explanation for this is that MRSA may also colonise the perineum or the throat, and this has been found to be the sole site of infection in some cases (Coello et al, 1994) so it is possible that sub-clinical carriers of MRSA were missed. Indeed, a study on humans in nursing homes indicated that up to 14% of cases are missed by screening the nares alone (Lee et al, 1997).…”
Section: E Horse Associated Mrsamentioning
confidence: 99%
“…32,33 Recently, high prevalence of the CoN staphylococci was found in healthy horses in Europe. 4,28,26 However, no MRSA strains have been isolated. No cases of nasal colonization of horses with MRS have been described in Italy.…”
mentioning
confidence: 99%